2019
DOI: 10.1002/jsfa.10136
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of antioxidant peptides from Chinese dry‐cured mutton ham

Abstract: BACKGROUND: Chinese mutton ham is a dry-cured meat product with a long ripening time. The aim of this study was to identify and characterize antioxidant peptides from Chinese mutton ham. RESULTS: Mutton ham peptides (MHPs) were purified by gel filtration, anion exchange and reversed-phase high-performance liquid chromatography steps. The 2,2 ′ -azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt (ABTS) free radical scavenging capacity was used to guide the purification of MHPs. Three antioxidant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 42 publications
2
12
0
Order By: Relevance
“…Antioxidant results indicated that the chicken, cherry valley duck, crossbred duck and other poultry meats could be potential sources of nutritional components and dietary antioxidants by reducing the oxidative damage associated with many diseases (Mohammed et al, 2020; Zhang et al, 2020). Wang et al (2020) also identified and characterised antioxidant peptides from Chinese mutton ham, which the three peptides exhibited great ability to inhibit lipid oxidation and DNA damage. These antioxidant experimental data indicated the protein extracts and peptides from the poultry and livestock could be used as a potential functional food and an excellent animal source of natural antioxidants.…”
Section: Resultsmentioning
confidence: 99%
“…Antioxidant results indicated that the chicken, cherry valley duck, crossbred duck and other poultry meats could be potential sources of nutritional components and dietary antioxidants by reducing the oxidative damage associated with many diseases (Mohammed et al, 2020; Zhang et al, 2020). Wang et al (2020) also identified and characterised antioxidant peptides from Chinese mutton ham, which the three peptides exhibited great ability to inhibit lipid oxidation and DNA damage. These antioxidant experimental data indicated the protein extracts and peptides from the poultry and livestock could be used as a potential functional food and an excellent animal source of natural antioxidants.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the amino acid sequences of peptides that play a key antioxidant role in several regional types of ham have been identified; these are AEEEYPDL, SNAAC, GLAGA, and SAGNPN (Spanish dry-cured ham) [ 105 , 106 , 107 ], GKFNV and LPGGGHGDL (Chinese Jinhua ham) [ 108 ] and DLEE (Chinese Xuanwei ham) [ 109 ]. Also, three short peptides MWTD, APYMM, and FWIIE with ABTS •+ scavenging antioxidant capacity (IC 50 0.40, 0.12, and 0.23) were described as characteristic antioxidant peptides formed during the ripening of Chinese dry-cured mutton ham [ 110 ]. Interestingly, these peptides are produced naturally during ham maturation, which means that they are the result of proteolytic phenomena exerted by intramuscular peptidases [ 111 ].…”
Section: Sources Of Antioxidant Peptidesmentioning
confidence: 99%
“…The MDPs could be obtained from various meat types including, bovine, chicken, pork, mutton and duck (Escudero et al ., 2010; Li et al ., 2020; Wang et al ., 2020). These MDPs could also be generated from fermented meat products like dry‐cured mutton, Spanish and Xuanwei ham (Castellano et al ., 2016; Xing et al ., 2016; Wang et al ., 2020). The bioactive peptides usually hide in the parental protein's primary structure, and can only be released upon enzymatic digestion in vitro or within the human gut.…”
Section: Introductionmentioning
confidence: 99%